Exploring the scope of vlogs in strengthening the delivery of medical education - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Medical Journal of Babylon, 2023)
With the passage of time, a number of curricular reforms have been introduced in the process of delivery of medical education. A video blog is a type of blog which utilizes the video medium to reach the audience. The purpose of the current review is to explore the role of video logs in strengthening the delivery of medical education. An extensive search of all materials related to the topic was carried out on the PubMed search engine and a total of 13 articles were selected based upon their suitability with the current review objectives and analyzed. Keywords used in the search include video blogs, and medical education in the title alone only. The video blogs have immense scope in the field of medical education, as it is one of an essential tool to promote student-centered learning, and enables the medical student to learn at their pace, and that too at their time of convenience. The need of the hour is that vlogs are integrated within the curriculum on a pilot basis, and research work is carried out to explore their benefit in terms of improving the attainment of knowledge and student engagement. Further, based on the obtained results, we can make modifications and eventually introduce vlogs in a structured manner in the curriculum. To conclude, vlogs are a widely used mode to share information on the online platform, nevertheless, it is high time that its utility is also explored and harnessed for improving the delivery of medical education. This calls for the need of all the stakeholders to take active steps and simultaneously plan for its inclusion and implementation in the teaching-learning process.